RAPID ASSESSMENT OF CRITICAL FACILITIES TO EARTHQUAKE DISASTER : HOSPITAL PREPAREDNESS IN WEST JAVA PROVINCE, INDONESIA AND ITS IMPLICATION FOR DISASTER RISK COMMUNICATION - Farah Mulyasari; Mohammad Rachmat Sule; dr. Kerti Sakinah (Jurnal Komunikasi & Media Digital, 2023)
Hospitals as critical health facilities, play an important role in the economical and psychological healing of the community following a disaster. Hospitals are crucial because they save lives in the afflicted community, and they must be able to endure dangers and continue to function during and after a disaster. Using a questionnaire survey, this study examines the earthquake preparedness of hospitals in West Java Province. The questionnaire consists of four pillars of hospital preparedness in terms of structural, non-structural, functional, and human resources that includes six parameters, and 24 indicators. This research uses lessons from the potential earthquake risk in southern part of West Java to analyse the level of disaster preparedness as well as the gaps for these hospitals in West Java regions. This status and the gaps serve as a starting point for determining how to enhance preparedness and resilience to future catastrophic earthquake disasters threats through disaster risk communication.